Eco-Efficiency of Coal-Fired Power Plants in the Java-Bali Grid - Firmandi Christiawan Djatmiko; Nur Aini Hidayati (Cakrawala Repositori IMWI)
Indonesia’s electricity sector remains heavily dependent on coal-fired power plants (CFPPs), which play a crucial role in maintaining the reliability of the national electricity supply, particularly within the Java–Bali power system. However, this dependence also contributes significantly to environmental emissions and pollution. This study aims to measure and analyze the eco-efficiency of coal-fired power plants operated by PT X within the Java–Bali grid during the 2023–2025 period. The research employs a quantitative approach using Data Envelopment Analysis (DEA) with the Slack-Based Measure (SBM) and Directional Distance Function (DDF) models. The input variables include fuel costs, maintenance costs, labor costs, and depreciation costs, while the outputs consist of electricity generation as the desirable output and SO?, NOx, and particulate emissions as undesirable outputs. The results indicate that most power plant units achieved relatively high eco-efficiency levels, with several Decision-Making Units (DMUs) reaching the efficiency frontier. JATIM 1 and JATIM 3 power plants demonstrated the highest and most consistent eco-efficiency performance, whereas JABAR and JATIM 2 exhibited greater fluctuations in efficiency. Slack analysis revealed that the primary sources of inefficiency were excessive input utilization and emission levels exceeding optimal benchmarks during certain operational periods. These findings suggest that improvements in eco-efficiency can be achieved through resource optimization, enhanced technical efficiency, strengthened emission control measures, and the implementation of energy transition strategies, such as biomass co-firing. This study provides valuable insights for industry practitioners and policymakers in promoting more efficient and sustainable power generation management.